Wiedza dotycząca zrównoważonego rozwoju wśród młodzieży licealnej na podstawie badań pilotażowych - Ilona Żeber-Dzikowska (Studia Ecologiae et Bioethicae)
The balanced development is at present the challenge for creating the awareness not only of the particular society, but also in the widest sense for the whole generation of the people. Undertaking such issues, the role of education during all stages of teaching, should be taken into consideration, especially, in the range of propagating the idea of responsibility for the natural environment with eco-development. It is a specially important element of teaching according to the principle of pro-environmental education to undertake all actions in the educational centers, which aim is to stimulate the environmental awareness of young people as well as to prepare the pedagogical staff to the realization of the wide range of methods and strategies that allow to get the best results during the process of educating young generation.